1995
DOI: 10.1111/j.1469-8749.1995.tb11932.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis of Specific Language Impairment: Evidence From a Twin Study

Abstract: SUMMARY Concordance rates were compared for 63 monozygotic (MZ) and 27 dizygotic (DZ) same‐sex twin pairs, aged seven years and over, selected because at least one twin met diagnostic criteria for specific speech or language impairment. There was significant heritability for developmental speech and language disorder, defined according to DSM‐III‐R criteria. When the definition of the phenotype was broadened to include those with a past history of disorder and those with a less pronounced discrepancy between v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0
25

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(138 citation statements)
references
References 23 publications
4
109
0
25
Order By: Relevance
“…For children with remaining difficulties at school-start, the prevalence rate has been found to be 1 % for severe and 4-5% for mild to moderate problems with language (Bishop, North & Donlan, 1996).…”
Section: Prevalence Of Language Delaymentioning
confidence: 99%
See 1 more Smart Citation
“…For children with remaining difficulties at school-start, the prevalence rate has been found to be 1 % for severe and 4-5% for mild to moderate problems with language (Bishop, North & Donlan, 1996).…”
Section: Prevalence Of Language Delaymentioning
confidence: 99%
“…Furthermore, it has been established that non-word repetition is strongly associated with both spoken language impairment and reading impairment (e.g. Bishop, North & Donlan, 1996, Stackhouse, 2000, Reuterskiöld-Wagner et al, 2005. This seems to hold true for the children with LD in the present study.…”
Section: Is There An Increased Risk Of Reading and Writing Difficulties?mentioning
confidence: 99%
“…Subsequent twin studies indicated an increase in concordance rates of MZ twin pairs over that of DZ twins, suggesting that much of the familial aggregation can be attributed to genetic influences (Lewis & Thompson, 1992;Bishop et al 1995;Tomblin & Buckwalter, 1998;Viding et al 2004). Furthermore, heritability of language ability has been suggested to increase as a function of the severity of language impairment.…”
Section: Introductionmentioning
confidence: 99%
“…No obstante, desde el punto de vista genético, hay que recordar que el lenguaje es un fenómeno muy complejo de modo que, en la gran mayoría de los casos, los trastornos específicos del lenguaje obedecen a la interacción de múltiples genes (Sanjuán et al, 2010). Un alto porcentaje de concordancia para trastornos de lenguaje se observó en mellizos monocigotos, frecuentemente con similar patrón de alteración (Bishop, North y Donlan, 1995;Tomblin y Buckwalter, 1998;Castaño, 2003). Por otra parte, se ha observado mayor incidencia de trastornos del lenguaje en niños con hiperplasia adrenal congénita, hallazgo que ha generado la sospecha de que existe una asociación con el gen para este trastorno (Plante, Boliek, Binkiewicz y Erly, 1996;Castaño, 2003).…”
Section: Discussionunclassified